Definition of Sustainability Indicators Applicable to Educational Units - e Souza, Barbara Silva [UNESP]; de Souza, Ricardo Gabbay [UNESP]; Ferreira, Arthur Bispo [UNESP]; Fiore, Fabiana Alves [UNESP] (FapUNIFESP (SciELO), 2024)
Education is one of the main tools to lead to sustainable development and, for it to happen, the school environment must become a reference capable of influencing the community. In Brazil, environmental education is expected to be carried out at all levels of education, but educational units are not evaluated for the effectiveness of the sustainable actions they perform. This work develops sustainability indicators applicable to educational units in the Brazilian territory. The quantitative-qualitative research was conducted based on the adaptation of consolidated sustainability tools, double-validated by a Survey with specialists in sustainability and education. The resulting model was structured around three axes: management, physical structure, and education for sustainability, and has indicators in categories and subcategories (levels 1 and 2). The model can support the development of an environmental certification instrument and guarantee the quality of education for sustainability in formal education.
Definición de Indicadores de Sostenibilidad Aplicables a Unidades Educativas
Definição de Indicadores de Sustentabilidade Aplicáveis a Unidades Educacionais
Keywords: Educación ambiental; educación en Brasil; education in Brazil; Educação ambiental; educação no Brasil; Environmental education; escola sustentável; escuela sustentable; indicadores; indicator; sustainability; sustainable school; sustentabilidad; sustentabilidade